Identifying information and communication technology use capacity needs of extension networks - Lamm, Kevan W.; Lamm, Alexa J.; Davis, Kristin E.; Swaroop, B. Jyothi; Edgar, Leslie D. (Association for International Agricultural and Extension Education, 2019)
Information and Communication Technology (ICT) has the potential to address critical considerations within rural advisory service (RAS) networks, specifically, getting the right information to audiences in a timely and appropriate manner. ICTs are technologies that facilitate knowledge and information sharing. For RAS networks, ICTs can be an important tool to ensure that both explicit and tacit information is shared with network members with the anticipated benefit of increased capacity of the network. Although the importance of ICTs are well documented within the literature, there are limited guidelines for what specific network capacities in ICT use are needed to better provide support for RAS providers to fulfill their responsibilities. Using the Delphi process, a panel of 31 experts from 24 countries arrived at consensus on 51 specific ICT use capacities associated with effective RAS networks. The results of the research provide a practical framework for RAS providers and networks to develop ICT use related capacity building and tactical planning activities.